Virtual learning and higher education - Preston, David Seth. (Amsterdam ; New York : Rodopi, 2004)
It is clear that the Internet and other global information infrastructures provide a major challenge to Higher Education. Questions such as: the extent to which education should become 'virtual', the actual cost and value of such innovation and to what degree such education suits its stakeholders (e.g. students) are now discussed the world over. These issues formed the focus for a conference held at Mansfield College, Oxford in September 2002 and this book contains the most rounded and challenging papers from that event. The book is divided into three main parts which consist of the following themes within Higher Education: current practical and planned uses for Virtual Learning; the future 'Virtual' vision; and the large questions that remain unanswered behind 'Virtual Education'. The contributors range from the nerdy end of experimenters of futuristic innovative technologies via the practitioner middle of well-known organizers of existing virtual systems to the other extreme of the critical engagement of philosophers. This stimulating and important book is aimed at researchers of topics such as technology-driven Education, Philosophy, Innovation and Cultural Studies. It is also meant to appeal to anyone with interest in the impact that the technological virtual will have upon Higher Education in future.
Preliminary Material / David Seth Preston -- Preface / D.S. Preston -- Frontierland: Exploring the Uses of Virtual Learning Environments in Higher Education / David Seth Preston -- Learning to Teach, Teaching to Learn: A Developmental Framework far Teacher Training / Mike Waring and Kate Boardman -- The Virtual Seminar / Melissa Lee Price and Andy Lapham -- Going From Distanee to Digital: Athabasca University's E-Learning Plan / Lynda R. Ross and Alan Davis -- Online Resouree Page: Using Technology to Enhanee Online Interactivity / Brent Muirhead -- Into the Unknown: Charting the Future of Virtual Learning Environments in Higher Education / David Seth Preston -- Working and Learning Together: ICT-Supported Learning in Small Businesses / Craig Thomson -- Strategie and Pedagogie Requirements for Virtual Learning in the Context of Widening Partieipation / Mark Stiles -- Assessment for Real in Virtual Learning Environments -- How Far Can We Go? / Mike Fuller -- Looking Before Leaping: Issues In Virtual Higher Education / David Seth Preston -- C.P. Snow Revisited: The Two Cultures of Faculty and Administration / James Wood -- Atatvistic Avatars: Ontology, Education and 'Virtual Worlds' / Adrian Bromage -- Virtual Values: The University in E-Crisis / David Seth Preston -- Notes on Contributors / David Seth Preston -- Index / David Seth Preston.
"One of the main products of a conference entitled 'Virtual Learning and Higher Education' held at Mansfield College (Oxford) in September 2002"--Preface
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Internet in higher education -- Congresses; Education, Higher -- Effect of technological innovations on -- Congresses; Distance education -- Computer-assisted instruction -- Congresses; Educational technology -- Congresses; Internet dans l'enseignement supérieur -- Congrès.; Enseignement supérieur -- Effets des innovations sur -- Congrès.; Enseignement à distance -- Enseignement assisté par ordinateur -- Congrès.; Technologie éducative -- Congrès.; EDUCATION -- Higher; Distance education -- Computer-assisted instruction; Education, Higher -- Effect of technological innovations on; Educational technology; Internet in higher education; Conference papers and proceedings